C and Sr isotopic evolution of carbonate sequences in NW Argentina: Implications for a probable Precambrian-Cambrian transition - Sial, A. N. (2001)
Upper Precambrian-Lower Cambrian sequences in the Tucuman, Salta and Jujuy provinces, NW Argentina, comprise sandstone, slate, conglomerate and black limestone (Las Tienditas/Volcan Fms.) with abundant Vendian/Tommotian trace fossils in the clastic facies rocks. The Precordillera basin, San Juan province, represents a continuous carbonate sequence belonging to the Lower to Middle Cambrian La Laja Fm. The Pie-de-Palo Range, Pampean Range, characterized by carbonates intercalated with greenschist/amphibolite facies metaclastic rocks, forms a part of the Precordillera basement. The δ13C values in carbonates of the Las Tienditas Fm. show a gradual decrease from the base (+3.4 ‰PDB) to the top with a minimum of -1.6‰ observed at ∼15m from the top, the latter having a higher clay content. Carbonates in a 700m thick section within La Laja Fm. is marked by a slightly positive δ13C values at the base (marly) with a negative anomaly (-2.0‰) at ∼20 m above, followed by a small positive anomaly (+0.5‰) ∼100 m from the base. All the values above this point are around -0.5‰ with a negative anomaly (-2.0‰) recorded at ∼240m above the base. Seawater 87Sr/86Sr values define a non-monotonic increase (0.70870 - 0.71082) through the carbonates in Las Tienditas Fm. while the La Laja Fm carbonates vary from 0.70926 to 0.71030, with higher values at the base. C and Sr isotopes, thus suggest that the Las Tienditas carbonates record the Precambrian-Cambrian transition (∼15m from the top of studied section). The same is also evident at ∼30 m from the base of the La Laja Fm. The narrow range of δ13C variation (-1.4 to + 1.3‰) and 87Sr/86Sr in the 0.709-0.710 range for the Caucete Group carbonates of the Pie-de-Palo Range, although unequivocally, appear to be in consonance with a Vendian to Tommotian age, reinforced by the presence of the trace fossils Didymaulichnus and Gordia.